Sistemática de Passalus Fabricius, 1792 (Coleoptera: Scarabaeoidea: Passalidae) - Bevilaqua, Marcus Vinícius Oliveira (Entomologia, 2022)
Passalus Fabricius is the type genus of the family Passalidae and is among one of the oldest genera of Coleoptera. Described 230 years ago, this Neotropical taxon, has already undergone profound changes in its configuration and is currently the largest genus of the family with about 180 described species. It is also the genus that presents the greatest systematic problems, since Gravely's work in 1918, the genus has encompassed a series of other genera, which has made it large and morphologically heterogeneous, which makes it difficult to understand its limits. In order to provide stabilization for the taxon, some classification proposals were made, however, currently all subgroups of the genus are not considered monophyletic. This study aimed to reduce the subjectivity of previous classifications for the genus, and using the cladistic method, propose a new classification for the genus Passalus Fabricius sensu lato, as well as for Passalini. We also intend to increase the knowledge of the species that make up this large genus and for that we made descriptions and redescriptions of species and characters of systematic use, we provided images that facilitate the identification of these species and characters, we implemented new records of occurrence and historical discussions about some species. After analyzing specimens of species from the entire Neotropical region, it was possible to describe 16 new species, redescribe another 12, revalidate 5 species, update the diagnoses and occurrence records of several other species, as well as propose a new classification for Passalini, which now includes three new subtribes and 16 genera, 2 new and 4 revalidated, additionally, all known genera were redescribed. Here, we also propose a new interpretation of the evolution of characters of the epicranium of Passalini, which from the integumentary movement suffered in these groups, gave rise to a series of morphological modifications that can help to distinguish the different lineages of the tribe, the set of all these characters. cephalic, it was called the Mediofrontal Complex.